Resin composition and flexible copper-clad plate prepared from same
By using a blended resin composition of carboxy-saturated polyester resin, phenoloxy resin and liquid epoxy resin in the flexible copper clad plate, and using 1-cyanoethyl-2-ethyl-4-methylimidazole as the curing agent, the problem of insufficient aging resistance and wettability of flexible copper clad plates in the prior art is solved, and a flexible copper clad plate with high reliability and high peel strength is achieved.
Patent Information
- Application Number
- CN202411964782.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-30
AI Technical Summary
The existing epoxy adhesives with flexible copper clad plates are prone to chemical reactions or breakage, resulting in poor aging resistance and ion mobility resistance. At the same time, the wetting and filling properties of the copper foil during the production process are poor, which affects the reliability of the board.
Carboxy saturated polyester resin and phenoloxy resin are blended as the main resin, liquid epoxy resin is introduced, and 1-cyanoethyl-2-ethyl-4-methylimidazole is used as the curing agent to improve the wetting and filling properties of the resin composition to the copper foil, and avoid the decrease in the peel strength of the sheet caused by the residue of high boiling point solvents.
It improves the aging resistance and peel strength of flexible copper clad plates, ensures that they still have high performance after long-term treatment at high temperatures, and is suitable for high-reliability applications such as on-board power batteries.
Smart Images

Figure BDA0005218081150000101 
Figure BDA0005218081150000102 
Figure BDA0005218081150000111
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electronic circuit substrates, and in particular to a resin composition and a flexible copper-clad laminate prepared therefrom. Background Art
[0002] Flexible copper clad laminates are light, thin and flexible, and are used to make flexible printed circuit boards. According to the manufacturing process or product structure, flexible copper clad laminates can be divided into two-layer flexible copper clad laminates (also called adhesive-free flexible copper clad laminates) and three-layer flexible copper clad laminates (also called adhesive-type flexible copper clad laminates). Adhesive-free flexible copper clad laminates have only two layers of copper foil and polyimide, and have high reliability characteristics such as high heat resistance, high aging resistance, and resistance to ion migration. Adhesive-type flexible copper clad laminates have a layer of adhesive between the copper foil and the polyimide film, and the performance of the adhesive plays a decisive role in the performance of adhesive-type flexible copper clad laminates. At present, the epoxy adhesive commonly used for adhesive-type flexible copper clad laminates is made of carboxyl nitrile rubber toughened epoxy resin. The unsaturated double bond energy and covalent bond dissociation energy on the carboxyl nitrile rubber molecular chain are low, and it is easy to undergo chemical reactions or break under the action of heat, oxygen, light, etc. In addition, the carboxyl nitrile rubber has a high content of impurity ions such as chloride ions, which makes the aging resistance and ion migration resistance of epoxy adhesive flexible copper clad laminates poor.
[0003] CN107674388A discloses a resin composition, including a carboxyl polyester resin, a multifunctional epoxy resin, a nitrogen-containing epoxy compound, a flame retardant and a solvent. The adhesive film, the covering film and the copper-clad laminate prepared by the resin composition have the advantages of being halogen-free, high temperature resistant, high temperature resistant, aging resistant, excellent in flexibility and high in peel strength. However, the amount of carboxyl polyester resin used in the patent is very high, the multifunctional epoxy resin used is all solid, the melting temperature of the overall resin composition is high, and the problem of continuous production, low rolling temperature, and poor wettability and filling of the resin composition on the rough surface of copper foil is ignored.
[0004] CN103483586A discloses a modified polyimide resin as a toughening agent for epoxy resin; CN107793702A discloses a resin composition for adhesive film and covering film, the resin composition comprising polyamide-imide resin, epoxy resin and phosphorus-containing phenolic resin. Both of these resin compositions with polyamide-imide resin as the main body do not contain carboxyl nitrile rubber, and have excellent heat aging resistance. The adhesive film or covering film made of them has the characteristics of high Tg, high heat resistance and good flame retardancy. However, the material cost of polyimide resin composition and polyamide-imide resin composition is relatively high, which limits their large-scale promotion and application.
[0005] CN116410684A discloses a resin composition and a covering film prepared therefrom, comprising a carboxyl-containing polyester resin, a phenolic resin, a multifunctional epoxy resin (all in solid state), and a 2,4-diamino-6-[2-(2-methyl-1-imidazole)ethyl]-S-triazine curing agent. The prepared covering film still has high peel strength, excellent heat aging resistance and chemical resistance after long-term treatment at high temperature. However, when the covering film is applied to a flexible copper-clad laminate and cured, microbubbles will appear on the board surface, and the peel strength of the copper foil is low.
[0006] As the application scenarios of electronic products put forward reliability requirements for flexible printed circuit boards, high reliability requirements are also put forward for flexible copper clad laminates. Therefore, it is of practical significance to improve the reliability of adhesive-type flexible copper clad laminates and thus improve the safety and reliability of electronic products. Summary of the invention
[0007] In order to solve the above technical problems, the present invention provides a resin composition and a flexible copper-clad laminate prepared therefrom. The present invention adopts a carboxyl saturated polyester resin and a phenolic resin blend as the main resin, introduces a liquid epoxy resin, and effectively improves the wettability and filling property of the copper foil; at the same time, 1-cyanoethyl-2-ethyl-4-methylimidazole is used to avoid the problem of solvent residues caused by the use of high-boiling point solvents leading to a decrease in the peel strength of the sheet. The copper-clad laminate prepared by the obtained resin composition has no apparent bubble generation, high peel strength, and excellent aging resistance, and is very suitable for high-reliability application fields such as vehicle-mounted power batteries.
[0008] To achieve this object, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a resin composition, comprising the following components in parts by weight:
[0010] 40-50 parts of carboxyl saturated polyester resin, 15-20 parts of phenoloxy resin, 5-10 parts of liquid epoxy resin and 0.05-0.15 parts of 1-cyanoethyl-2-ethyl-4-methylimidazole.
[0011] The “parts” and “parts by weight” involved in the present invention are all calculated based on solid content and do not include solvents, dispersants, etc.
[0012] In the present invention, the carboxyl saturated polyester resin can be, for example, 40 parts, 42 parts, 44 parts, 46 parts, 48 parts, 50 parts, etc.; the phenoloxy resin can be, for example, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, etc.; the liquid epoxy resin can be, for example, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, etc.; the imidazole curing agent can be, for example, 0.05 parts, 0.06 parts, 0.08 parts, 0.1 parts, 0.12 parts, 0.14 parts, 0.15 parts, etc.
[0013] The invention adopts a carboxyl saturated polyester resin and a phenolic resin as a main resin, and endows the resin composition with excellent aging resistance; by introducing a small molecule epoxy resin (i.e., liquid epoxy resin) which is liquid at room temperature, the wettability and filling property of the copper foil are effectively improved, and the defects of the carboxyl saturated polyester resin and the phenolic resin being poor in wettability and filling property of the rough surface of the copper foil under low rolling temperature in the continuous production of the adhesive-type flexible copper-clad laminate due to high melting viscosity, and the defects of the plate being not compacted and the peeling strength being low are overcome; at the same time, 1-cyanoethyl-2-ethyl-4-methylimidazole is adopted as a specific imidazole curing agent, and the substance can be dissolved in a low boiling point solvent, and the problem of the resin composition remaining in the adhesive layer due to the use of a high boiling point solvent and incomplete volatilization during coating, resulting in a decrease in the peeling strength of the plate and sub-apparent microbubbles is effectively avoided.
[0014] In the present invention, the carboxyl saturated polyester resin has excellent heat aging resistance and heat resistance, and can react with liquid epoxy resin because it contains carboxyl. If the amount of carboxyl saturated polyester resin is too much, the glass transition temperature of the resin composition is low, and the bending resistance of the flexible copper clad laminate prepared therefrom is poor; if the amount of carboxyl saturated polyester resin is too little, the softness and adhesion of the resin composition will decrease.
[0015] In the present invention, the phenolic resin is an ultra-high molecular weight epoxy resin with a high glass transition temperature, which can improve the flexibility, modulus and glass transition temperature of the resin composition. If the amount of phenolic resin is too much, the adhesion of the resin composition decreases; if the amount of phenolic resin is too little, the modulus and glass transition temperature of the resin composition are low, and the bending resistance of the flexible copper clad laminate decreases.
[0016] In the present invention, the liquid epoxy resin refers to a low molecular weight epoxy resin that is liquid at room temperature, which not only reacts with the carboxyl saturated polyester resin, but also helps to improve the wetting and filling performance of the resin composition on the rough surface of the copper foil during roll lamination. If the amount of liquid epoxy resin is too much, the amount of the corresponding carboxyl saturated polyester resin, phenolic resin and other macromolecular resins will decrease, and the flexibility of the resin composition will decrease; if the amount of liquid epoxy resin is too little, the amount of the corresponding carboxyl saturated polyester resin, phenolic resin and other macromolecular resins will increase, and the wettability and filling performance of the resin composition on the rough surface of the copper foil will decrease.
[0017] In the present invention, the 1-cyanoethyl-2-ethyl-4-methylimidazole can be used as a curing agent for liquid epoxy resin and also as an accelerator for the reaction between carboxyl saturated polyester resin and epoxy resin. The use of the substance effectively avoids the defect that the resin composition uses a high-boiling point solvent and incomplete volatilization during coating causes the resin composition to remain in the adhesive layer, resulting in a decrease in the peeling strength of the board.
[0018] Preferably, the resin composition further comprises an organic solvent.
[0019] Preferably, the solid content of the organic solvent added to the resin composition is 35-45%, for example, 35%, 36%, 38%, 40%, 42%, 44%, 46%, etc.
[0020] Preferably, the boiling point of the organic solvent is ≤100°C, for example, it may be 10°C, 20°C, 50°C, 80°C or 90°C.
[0021] Preferably, the organic solvent includes any one of butanone, acetone or ethyl acetate, or a combination of at least two of them.
[0022] Preferably, the residual solvent content of the semi-cured resin composition obtained after the resin composition is partially cross-linked and cured by heating is ≤0.5%, for example, it can be 0.45%, 0.4%, 0.35%, 0.3%, 0.25%, 0.2%, 0.15%, 0.1%, 0.05%, etc.
[0023] The heating described in the present invention is heating at 80-160°C (for example, it can be 80°C, 100°C, 120°C, 140°C, 160°C, etc.) for 2-5min (for example, it can be 2min, 2.5min, 3min, 3.5min 4min, 4.5min, 5min, etc.) to make the resin composition partially cross-linked and cured to obtain a semi-cured resin composition, and then test the residual solvent content.
[0024] In the present invention, by selecting a low boiling point solvent, the resin composition has a low residual solvent content of volatile components after being partially cross-linked and cured by heating. When applied to a copper clad laminate, no bubbles are generated on the surface, and the obtained copper clad laminate has a high peeling strength.
[0025] Although increasing the oven drying temperature can reduce the residual solvent rate, high temperature will also accelerate the cross-linking reaction of the resin composition, increase the melt viscosity of the resin composition, and thus deteriorate the wettability and filling properties of the rough surface of the copper foil, resulting in a decrease in the peel strength of the board. In the cover film product, the high-boiling point solvent remaining in the resin layer can be removed during the baking process through the microscopic pores in the polymer base film and the release paper protective layer, while in the flexible copper clad laminate, since the dense structure of the copper foil does not have the aforementioned exhaust microscopic pores, the solvent residue is likely to cause micro bubble defects on the sub-surface of the board.
[0026] Preferably, the acid value of the carboxyl saturated polyester resin is 10-25 mgKOH / g, for example, 10 mgKOH / g, 14 mgKOH / g, 18 mgKOH / g, 22 mgKOH / g, 25 mgKOH / g, etc.
[0027] In the present invention, the carboxyl saturated polyester resin contains carboxyl groups and has a high acid value and high reactivity, and can react with the liquid epoxy resin.
[0028] Preferably, the number average molecular weight of the carboxyl saturated polyester resin is 5000-20000, for example, 5000, 8000, 10000, 14000, 16000, 20000, etc.
[0029] Preferably, the weight average molecular weight of the phenoloxy resin is 45000-65000, for example, 45000, 48000, 54000, 58000, 62000, 65000, etc.
[0030] For example, the number average molecular weight and the weight average molecular weight can be measured according to GB / T 21863-2008 and measured by gel permeation chromatography (GPC method) based on polystyrene calibration.
[0031] Preferably, the liquid epoxy resin includes any one of bisphenol A epoxy resin, bisphenol F epoxy resin, glycidyl ester epoxy resin or glycidyl amine epoxy resin, or a combination of at least two of them.
[0032] Preferably, the epoxy equivalent of the liquid epoxy resin is 80-200 g / eq, for example, 80 g / eq, 100 g / eq, 120 g / eq, 140 g / eq, 160 g / eq, 180 g / eq, 200 g / eq, etc.
[0033] In the present invention, the liquid epoxy resin refers to an epoxy resin that is liquid at a temperature of 20° C. For example, the determination of the liquid and solid in the epoxy resin can be carried out according to the "Method for Confirming the Liquid State" in Appendix 2 of the Ministerial Order on the Test and Properties of Dangerous Goods (Ministerial Order No. 1 of the first year of Heisei), and the specific determination method in CN118325282A can be referred to for details.
[0034] Preferably, the resin composition further comprises 10-20 parts of a phosphorus-containing flame retardant, for example, 10 parts, 12 parts, 14 parts, 16 parts, 18 parts, 20 parts, etc.
[0035] Preferably, the phosphorus-containing flame retardant includes any one of diethyl aluminum phosphinate, melamine polyphosphate or hexaphenoxy cyclotriphosphazene, or a combination of at least two thereof.
[0036] Preferably, the resin composition further comprises 5-10 parts of inorganic filler, for example, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, etc.
[0037] Preferably, the inorganic filler includes any one of aluminum hydroxide, magnesium hydroxide, boehmite, talc, silicon dioxide, kaolin or alumina, or a combination of at least two thereof.
[0038] Preferably, the resin composition further comprises 0.2-0.5 parts of an antioxidant, for example, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, etc.
[0039] Preferably, the antioxidant comprises a hindered phenol antioxidant and / or a hindered amine antioxidant.
[0040] In the present invention, the antioxidant can delay the oxidation of the epoxy resin composition during high temperature curing and subsequent processing and application. The antioxidant used includes but is not limited to any one of the hindered phenol antioxidants CHINOX 1010, CHINOX 1076, CHINOX 1098, CHIN0Z 1325 (all manufactured by Double Bond Chemical Co., Ltd.) or the hindered amine antioxidant DNP (manufactured by Kaiyuan Fine Chemicals) or a combination of at least two thereof.
[0041] In a second aspect, the present invention provides a resin film, wherein the material of the resin film includes the resin composition as described in the first aspect.
[0042] Preferably, the resin film is obtained by coating the resin composition on a release material and then drying and / or semi-curing the resin composition.
[0043] In a third aspect, the present invention provides a flexible copper clad laminate, comprising a base film, and a resin layer located on one or both sides of the base film, wherein a copper foil is provided on the surface of the resin layer; the resin layer is a coating of the resin composition as described in the first aspect.
[0044] Preferably, the base film comprises a polyimide film.
[0045] Preferably, the base film has a thickness of 12.5-50 μm, for example, 12.5 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, etc.
[0046] Preferably, the thickness of the resin layer is 10-50 μm, for example, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, etc.
[0047] Preferably, the copper foil has a thickness of 12-70 μm, for example, 12 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, etc.
[0048] Exemplarily, the method for preparing the flexible copper clad laminate of the present invention comprises: coating the resin composition on one side or both sides of a base film and drying; then rolling copper foil on the surface of the resin composition and curing to obtain the flexible copper clad laminate.
[0049] Preferably, the drying temperature is 80-160°C, for example, 80°C, 100°C, 120°C, 140°C, 160°C, etc.
[0050] Preferably, the drying time is 2-5 min, for example, 2 min, 2.5 min, 3 min, 3.5 min, 4 min, 4.5 min, 5 min, etc.
[0051] Preferably, the temperature of the rolling is 70-90°C, for example, 70°C, 75°C, 80°C, 85°C, 90°C, etc.
[0052] Preferably, the curing temperature is 160-180°C, for example, 160°C, 165°C, 170°C, 175°C, 180°C, etc.
[0053] Preferably, the curing time is 1.5-2.5 h, for example, it can be 1.5 h, 1.6 h, 1.8 h, 2 h, 2.2 h, 2.4 h, 2.5 h, etc.
[0054] Compared with the prior art, the present invention has at least the following beneficial effects:
[0055] The present invention adopts a carboxyl saturated polyester resin and a phenolic resin as a main resin, thereby giving the resin composition excellent aging resistance; by introducing a small molecule epoxy resin (i.e., liquid epoxy resin) that is liquid at room temperature, the wettability and filling property of the copper foil are effectively improved; and at the same time, 1-cyanoethyl-2-ethyl-4-methylimidazole is adopted as a specific imidazole curing agent, thereby effectively avoiding the problem that the resin composition uses a high-boiling point solvent and is not completely volatilized during coating, thereby remaining in the adhesive layer, resulting in a decrease in the peeling strength or heat resistance of the board.
[0056] The resin composition provided by the present invention has less residual solvent after heating and curing, and has good wettability to copper foil. When applied to a copper clad laminate, no bubbles are generated on the surface. At the same time, the peel strength of the prepared copper clad laminate reaches 1.61-1.68N / mm, and can still reach above 1.46N / mm after high-temperature treatment at 125°C for 1000h. It has excellent aging resistance and is suitable for high-reliability application fields such as vehicle-mounted power batteries. DETAILED DESCRIPTION
[0057] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0058] The sources of materials used in the following examples are as follows:
[0059] Carboxyl saturated polyester resin, brand RV-74SS, Toyobo Co., Ltd., acid value 17 mgKOH / g, number average molecular weight 16000;
[0060] Carboxyl saturated polyester resin, brand AL-148, Suzhou Hanhai New Materials Co., Ltd., acid value is 15 mgKOH / g, number average molecular weight is 15000;
[0061] Phenoloxy resin, brand 1276, Mitsubishi Chemical Corporation, weight average molecular weight 51000;
[0062] Phenoloxy resin, brand PKHJ, InChem Corporation, weight average molecular weight 57000;
[0063] Bisphenol A epoxy resin 1, liquid, brand GELR128E, epoxy equivalent 185g / eq, Hongchang Electronic Materials Co., Ltd.;
[0064] Bisphenol A epoxy resin 2, solid, brand GESR901, epoxy equivalent 465g / eq, Hongchang Electronic Materials Co., Ltd.;
[0065] Bisphenol F epoxy resin 1, liquid, brand KF-8100, epoxy equivalent 170g / eq, KOLON INDUSTRIES;
[0066] 1-Cyanoethyl-2-ethyl-4-methylimidazole, Shikoku Chemical Co., Ltd.;
[0067] Aluminum diethylphosphinate, brand OP-935, Clariant;
[0068] Boehmite, grade APYRAL AOH 60, Nabaltec AG;
[0069] Antioxidant 1010, brand name CHINOX 1010, Double Bond Chemical Company;
[0070] 2,4-Diamino-6-[2-(2-methyl-1-imidazole)ethyl]-s-triazine, Shanghai Haodeng Materials Co., Ltd.;
[0071] 2-Undecylimidazole, Shikoku Chemical Co., Ltd.
[0072] Examples 1-3, Comparative Examples 1-3
[0073] The above-mentioned embodiments and comparative examples respectively provide a resin composition, whose components and dosage (solid weight parts) are shown in Table 1 and Table 2. The solid components are dissolved and dispersed in an organic solvent according to the ratios in Table 1 and Table 2 to obtain resin compositions with a solid content of 40%.
[0074] The resin compositions provided in Examples 1-3 and Comparative Examples 1-3 were respectively coated on a polyimide film with a thickness of 25 μm (GF05, PI Advanced Materials Co., Ltd.) using a coating machine, and the thickness of the resin composition layer was controlled to be 38 μm. The film was then placed in an oven at 140°C and baked for 3 min to form a partially cross-linked and cured resin composition layer on the polyimide film. The film was then roll-compounded with a 35 μm rolled copper foil (BHYX, Nippon Mining and Metals Co., Ltd.) at a rolling temperature of 80°C to form a single-sided flexible copper clad laminate semi-finished product. The above-mentioned coating, baking, and rolling composite processes were repeated on the PI film surface of the single-sided flexible copper clad laminate semi-finished product to form a double-sided flexible copper clad laminate semi-finished product. The film was finally cured at 170°C for 2 h to obtain a finished flexible copper clad laminate.
[0075] Test Case
[0076] The residual solvent content of the semi-cured resin obtained after the resin compositions provided in Examples 1-3 and Comparative Examples 1-3 were heated and semi-cured, and the properties of the prepared flexible copper clad laminates were tested. The results are shown in Tables 1 and 2.
[0077] Table 1
[0078]
[0079] Table 2
[0080]
[0081]
[0082] The above performance test method is as follows:
[0083] (1) Residual solvent content:
[0084] The resin composition is coated on the surface of the polyimide film base film using a coating machine, dried in an oven, and heated at 140° C. for 3 minutes to remove the organic solvent and partially crosslink and cure the resin composition to form a semi-cured resin composition layer on the surface of the polyimide film base film.
[0085] The polyimide film base film was cut into pieces of 10 cm×10 cm, and the weight was measured using an electronic balance. Three samples were measured, and the average value was taken as the mass of the polyimide film base film.
[0086] The carrier resin film (polyimide film base film + semi-cured resin composition layer) was cut into 10cm×10cm, and the initial mass was measured using an electronic balance. Next, the carrier resin film was placed on a metal mesh, heated in an oven pre-set to 200°C for 15 minutes, moved into a dryer, left to stand for 30 minutes, and cooled to room temperature. Then, an electronic balance was used to measure the post-baking mass of the carrier resin film. The initial mass and post-baking mass of all three samples were measured, and the average value was taken. The amount of solvent contained in the semi-cured resin layer (residual solvent amount) was calculated using the following formula:
[0087] Residual solvent amount (mass %) = 100 x (initial mass of carrier resin film - mass of carrier resin film after baking) / (initial mass of carrier resin film - mass of polyimide film base film).
[0088] (2) Peel strength: tested according to IPC-TM-650 2.4.9 method, received state (state A).
[0089] (3) Heat aging resistance: The sample was placed in an oven at 125°C and baked for 1000 h, then taken out to test the peel strength. The test condition was E-1000 / 125.
[0090] (4) Secondary appearance: After etching the copper foil of the flexible copper clad laminate, the secondary surface of the board should be visually inspected to see if there are any defects such as micro bubbles, glue deficiency, white spots, and debris.
[0091] It can be seen from Examples 1-3 that the resin composition provided by the present invention has less residual solvent after heating and curing, and has good wettability to copper foil. When applied to copper clad laminates, no bubbles are generated on the surface; at the same time, the peel strength of the copper clad laminates obtained reaches 1.61-1.68N / mm, and can still reach above 1.46N / mm after high-temperature treatment at 125°C for 1000h, showing excellent aging resistance.
[0092] By comparing Example 1 with Comparative Examples 1-3, it can be seen that solid bisphenol A epoxy resin is used in Comparative Example 1, and the wettability of the resin composition to the copper foil is poor during rolling, resulting in low peel strength of the board; Comparative Example 2 uses 2,4-diamino-6-[2-(2-methyl-1-imidazole)ethyl]-s-triazine instead of 1-cyanoethyl-2-ethyl-4-methylimidazole. Since 2,4-diamino-6-[2-(2-methyl-1-imidazole)ethyl]-s-triazine is difficult to dissolve in butanone and needs to be dissolved in dimethyl sulfoxide, a high-boiling-point solvent. When preparing a double-sided flexible copper clad laminate, the high-boiling-point solvent is not completely volatilized and remains in the adhesive layer. When the board is cured, problems such as microbubbles and reduced peel strength occur, resulting in poor aging resistance of the board; Comparative Example 3 uses 2-undecyl imidazole instead of 1-cyanoethyl-2-ethyl-4-methylimidazole, and the peel strength and heat aging resistance of the board are reduced.
[0093] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A resin composition, characterized in that The resin composition comprises the following components in parts by weight: 40-50 parts of carboxyl saturated polyester resin, 15-20 parts of phenoloxy resin, 5-10 parts of liquid epoxy resin and 0.05-0.15 parts of 1-cyanoethyl-2-ethyl-4-methylimidazole.
2. The resin composition according to claim 1, characterized in that The resin composition further comprises an organic solvent; Preferably, the solid content of the organic solvent added to the resin composition is 35-45%; Preferably, the boiling point of the organic solvent is ≤100°C; Preferably, the organic solvent includes any one of butanone, acetone or ethyl acetate, or a combination of at least two of them.
3. The resin composition according to claim 1 or 2, characterized in that The residual solvent content of the semi-cured resin composition obtained after the resin composition is partially cross-linked and cured by heating is less than or equal to 0.5%.
4. The resin composition according to any one of claims 1 to 3, characterized in that The acid value of the carboxyl saturated polyester resin is 10-25 mgKOH / g; Preferably, the number average molecular weight of the carboxyl saturated polyester resin is 5000-20000; Preferably, the weight average molecular weight of the phenoloxy resin is 45,000-65,000.
5. The resin composition according to any one of claims 1 to 4, characterized in that The liquid epoxy resin includes any one of bisphenol A epoxy resin, bisphenol F epoxy resin, glycidyl ester epoxy resin or glycidyl amine epoxy resin, or a combination of at least two thereof; Preferably, the epoxy equivalent of the liquid epoxy resin is 80-200 g / eq.
6. The resin composition according to any one of claims 1 to 5, characterized in that The resin composition further comprises 10-20 parts of a phosphorus-containing flame retardant; Preferably, the phosphorus-containing flame retardant includes any one of diethyl aluminum phosphinate, melamine polyphosphate or hexaphenoxy cyclotriphosphazene, or a combination of at least two thereof.
7. The resin composition according to any one of claims 1 to 6, characterized in that The resin composition further comprises 5-10 parts of inorganic filler; Preferably, the inorganic filler comprises any one or a combination of at least two of aluminum hydroxide, magnesium hydroxide, boehmite, talc, silicon dioxide, kaolin or alumina; Preferably, the resin composition further comprises 0.2-0.5 parts of an antioxidant; Preferably, the antioxidant comprises a hindered phenol antioxidant and / or a hindered amine antioxidant.
8. A resin film, characterized in that: The material of the resin film comprises the resin composition according to any one of claims 1 to 7; Preferably, the resin film is obtained by coating the resin composition on a release material and then drying and / or semi-curing the resin composition.
9. A flexible copper clad laminate, characterized in that: The flexible copper-clad laminate comprises a base film and a resin layer on one or both sides of the base film, wherein a copper foil is disposed on the surface of the resin layer; and the resin layer is a coating of the resin composition according to any one of claims 1 to 7.
10. The flexible copper clad laminate according to claim 9, characterized in that: The base film includes a polyimide film; Preferably, the thickness of the base film is 12.5-50 μm; Preferably, the thickness of the resin layer is 10-50 μm; Preferably, the copper foil has a thickness of 12-70 μm.
Citation Information
Patent Citations
Modified polyimide resin, adhesive composition containing modified polyimide resin and covering film containing adhesive composition
CN103483586A
Halogen-free resin composition, and glue film, cover film and copper-clad plates prepared from halogen-free resin composition
CN107674388A
Resin composition and gum film and cover film prepared from resin composition
CN107793702A
Resin composition
CN118325282A
Halogen-free resin composition and cover film, copper-clad plate and printed wiring board prepared from same
CN109135647A
Cited By
Resin composition, adhesive and FFC insulating adhesive film
CN121699348A